Effect of eight weeks high-fat diet with endurance training on plasma levels of Amylin in male Wistar rats - Mohammadreza kordi; Farzaneh Maleki; AliAsghar Ravasi; Sadegh Satarifard (Iranian South Medical Journal, 2016)
Background: Amylin is a polypeptide hormone prevents weight gain and obesity by loss of appetite. Therefore, the purpose of this study was the effect of eight weeks high-fat diet with endurance training on body weight and plasma levels of amylin in male wistar rats.